Personalized Remote Mobile Surveys of Adult ADHD Symptoms and Function: A Pilot Study of Usability and Utility for Pharmacology Monitoring. Issue 7 (May 2022) - Surman, Craig; Boland, Heidi; Kaufman, Daniel; DiSalvo, Maura
Objective: Validate the usability and treatment-sensitivity of a remote SMS-based ADHD monitoring method. Method: 206 adults taking stimulants for ADHD participated. Participants selected ADHD symptoms and functional impairments that they anticipated to be stimulant-sensitive, which were rated via mobile messages up to 20 times over 10 days. Results: A majority of participants found it only somewhat or not at all difficult to identify an ADHD symptom sensitive to presence of stimulant medication, and 79% responded to at least one survey message. As expected, a majority of participants endorsed it was "easy" to participate, and less burdensome than a paper diary. Surveys significantly discriminated between on and off medication states, both between days, and within the same day. Conclusion: Our findings suggest SMS-based monitoring of patient-selected ADHD-related challenges is both feasible and sensitive to stimulant treatment. This remote assay method may be a meaningful adjunct to in-visit treatment monitoring